Epidemiology and Diagnosis of Brain Tumors. Issue 2 (April 2015) - Butowski, Nicholas A.
Abstract : Purpose of Review: : Brain tumors consist of a collection of neoplasms arising from within the brain or from systemic tumors that have metastasized to the brain. This article focuses on the most recent findings with regard to epidemiology, clinical presentation, neuroimaging evaluation, and diagnosis of brain tumors. Recent Findings: : Patients with brain tumors may present for care with a variety of signs and symptoms. The most frequent clinical presentations include seizure, headache, fatigue, and cognitive dysfunction. Currently, diagnosis and treatment response is largely evaluated by using MRI. However, molecular imaging may ultimately be better suited to measuring early response by quantifying cellular metabolism, proliferation, and apoptosis, activities altered in treatment. Contemporary neuropathology continues to play a key role in the multidisciplinary management of patients with brain tumors. Genetic and environmental risk factors for brain tumors remain largely unclear. Summary: : Brain tumors represent a diverse spectrum of highly morbid cancers arising from different cells both from within the brain and from systemic tumors that have metastasized to the brain. The clinical manifestations of intracranial tumors are usually referable to the anatomic area of the brain involved or adjacent structures. The initial diagnosis of intracranial tumors is most efficiently made by imaging, generally MRI, although other techniques are being explored. The clinical manifestations, neuroimaging evaluation, and diagnosis of brain tumors are varied and dependent on the specific manner in which a patient presents for care. To date, specific causes of brain tumors remain elusive.